“English with a Polish Accent and a Slight Touch of Irish”: Multilingualism in Polish Migrant Theatre - Prykowska-Michalak, Karolina; Grabarczyk, Izabela (Text Matters: A Journal of Literature, Theory and Culture, 2023)
Issues of migration writing (see Kosmalska) and migrant theatre have recently gained prominence, leading to an increase in research focused on analyzing the theatrical works of artists with a migrant background. This phenomenon is part of a broader trend in intercultural and, often, postcolonial studies. Contemporary Polish migrant theatre is a subject that has not been thoroughly explored yet. Among many methods applied in the study of migrant theatre, intercultural studies or the so-called new interculturalism take the lead. These concepts draw on bilingualism or multilingualism practices, which are slowly taking a more significant role in migrant theatre studies. This article analyzes two theatre plays staged by Polish migrants in Ireland and in the United Kingdom in the context of linguistic practices that exemplify and help define the concept of transnational drama.